2010
DOI: 10.1210/en.2009-1002
|View full text |Cite
|
Sign up to set email alerts
|

Meal-Anticipatory Glucagon-Like Peptide-1 Secretion in Rats

Abstract: Animals anticipating a meal initiate a series of responses enabling them to better cope with the meal's metabolic impact. These responses, such as cephalic insulin, occur prior to the onset of ingestion and are especially evident in animals maintained on a meal-feeding schedule with limited but predictable access to food each day. We tested the hypothesis that meal-fed rats secrete the incretin hormone glucagon-like peptide-1 (GLP-1) cephalically when anticipating a large meal. Male Long-Evans rats were fed ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 48 publications
(46 reference statements)
0
55
0
1
Order By: Relevance
“…Circulating GLP-1 levels rise after a meal and fall in the fasted state. Recent evidence also suggests that levels rise in anticipation of a meal [96]. GLP-1 reduces food intake, suppresses glucagon secretion and delays gastric emptying [97].…”
Section: Ghrelinmentioning
confidence: 99%
“…Circulating GLP-1 levels rise after a meal and fall in the fasted state. Recent evidence also suggests that levels rise in anticipation of a meal [96]. GLP-1 reduces food intake, suppresses glucagon secretion and delays gastric emptying [97].…”
Section: Ghrelinmentioning
confidence: 99%
“…In rodents, a transient increase in GLP-1 levels was observed in anticipation of food being presented [52], suggesting a cephalic response. However, in humans, the balance of evidence suggests that vagal cholinergic innervation does not play a major role in regulating incretin hormone secretion.…”
Section: Neural Regulationmentioning
confidence: 99%
“…It has already been shown that incretin secretion from the bowel can be regulated by mechanisms other than direct nutrient stimulation. Increased GLP-1 secretion has been shown before an anticipated meal, and these phenomena are known as the cephalic phase of secretion [24]. Other nutrients and possibly any bolus that distends the small bowel can induce a GIP and GLP-1 response.…”
Section: Discussionmentioning
confidence: 99%